The Effects of the COVID-19 Pandemic on the Mental Health and Subjective Well-Being of Workers: An Event Study Based on High-Frequency Panel Data - Julia Schmidtke; Clemens Hetschko; Ronnie Schöb; Gesine Stephan; Michael Eid; Mario Lawes (Institute of Labor Economics (IZA), 2021)
Using individual monthly panel data from December 2018 to December 2020, we estimate the impact of the Covid-19 pandemic and two lockdowns on the mental health and subjective well-being of German workers. Employing an event-study design using individual-specific fixed effects, we find that the first and the second wave of the pandemic reduced workers' mental health substantially. Momentary happiness and life satisfaction also decline in response to Covid-19, but to a smaller extent. We observe adapation in our study outcomes between waves of the pandemic. This applies to a lesser extent to indicators of well-being in certain areas of life, such as satisfaction with the job and with leisure, which are negatively affected, too. Women do not seem to suffer greater well-being losses than men. However, workers in the German short-time work scheme are particularly negatively affected. Our results imply that increased anxiety about the future and restricted personal freedoms are among the drivers of the well-being impact of the pandemic.
Keywords: I31; I19; 330; Covid-19; life satisfaction; depression; affective well-being; app-based survey data; German Job Search Panel